Socio-cultural and ethno-educational values of rural national families in the Samara region (according to the results of sociological research) - Klyuyashkina I. N., Eroshkina T. P. (Humanitarian, 2017)
the article reveals the socio-cultural values, traditions and norms of national families in the Northern rural areas of the Samara region; provides wise advice on parenting, perceived by the national families from their parents.
Keywords: ценности; воспитание; традиции; область; values; region; traditions; upbringing; национальная семья; national family